Linagliptin- a novel dpp-iv inhibitor - N.PRABAVATHY; M.VIJAYAKUMARI; M.MINIL; U.SATHIYARAJ; S.KAVIMANI (International Journal of Pharma and Bio Sciences, 2011)
Although glycemic control is an important and effective way to prevent and minimize the worsening of diabetes-related complications, type 2 diabetes is a progressive disease which often proves difficult to manage. Most affected patients will eventually require therapy with multiple medications in order to reach appropriate glycemic targets. The dipeptidyl peptidase-4 (DPP-4) inhibitors constitute a relatively new class of oral medications for the treatment of type 2 diabetes, which has become widely incorporated into clinical practice. Linagliptin is a novel dipeptidyl peptidase-4 (DPP-4) inhibitor in clinical development for the treatment of type 2 diabetes. It exhibits non-linear pharmacokinetics and shows concentrationdependent plasma protein binding to its target, DPP-4.